Gypenosides mediate cholesterol efflux and suppress oxidized LDL induced inflammation in retinal pigment epithelium cells. (February 2020) - Biswas, Lincoln; Zeng, Zhihong; Graham, Annette; Shu, Xinhua
Abstract: Age-related macular degeneration (AMD) is a predominant cause of visual deficit in aged population. Abnormal accumulation of cholesterol, including oxidized low-density lipoprotein (oxLDL), underneath the retinal pigment epithelium (RPE) cells contributes to the development of AMD. Gypenosides (Gyp) are glycosides extracted from Gynostemma pentaphyllum and have demonstrated protective effects against inflammation and oxidative stress. To determine the therapeutic potential of Gyp for AMD, we investigated its effect on cholesterol trafficking and metabolism and assessed the protective function of Gyp against oxLDL-induced damage in RPE cells. Cholesterol efflux to high-density lipoprotein (HDL) and human serum was significantly increased in RPE cells treated with Gyp when compared to untreated control cells. Expression of cholesterol metabolism ( CYP27A1, CYP46A1 ) and trafficking ( TSPO, ABCA1 and ABCG1 ) genes was also markedly increased in Gyp-treated RPE cells. OxLDL-treated RPE cells had significantly increased cholesterol accumulation and lipid droplet formation. There were marked increases in reactive oxygen species (ROS) generation and proinflammatory cytokines via NF-κB activation in RPE cells treated with oxLDL, while incubation with Gyp rectified these changes. These findings provide pharmacological evidence that Gyp has the potential to treat patients with early onset AMD by promoting cellular cholesterol removal from RPE cells and inhibiting inflammation and oxidative stress. Highlights: Gypenosides enhance cholesterol efflux in retinal pigment epithelium cells. Gypenosides reduce uptake and accumulation of oxidized LDL in retinal pigment epithelium cells. Gypenosides suppress oxidized LDL induced ROS production in retinal pigment epithelium cells. Gypenosides inhibit oxidized LDL induced inflammation in retinal pigment epithelium cells.